Comparison of High Resolution Computed Tomography with Intraoperative Findings in Patient with Chronic Suppurative Otitis Media, NAMS, Bir Hospital, Kathmandu, Nepal - Rokaya, Yagya Bahadur; Shahi, Prakash (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Chronic suppurative otitis media (CSOM) is an important cause of middle ear disease and its complications challenge both otologist and radiologist. The major benefit of HRCT is an excellent visualization of the osseous structure by means of special algorithms. This study compares the HRCT with intraoperative findings in patients with CSOM.Methods: This is an observational descriptive study conducted at NAMS Bir Hospital. Total of 30 patients, referred for HRCT from the department of ENT were studied. Comparison of HRCT findings was done with intraoperative findings regarding the status of EAC, ossicular chain, bony plate, inner ear structure and facing nerve canal was done, considering intraoperative findings as the gold standard.Results: Out of 30 patients, 16 patients had CSOM with cholesteatoma and 14 patients had CSOM without cholesteatoma. HRCT presented sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 87.5%, 85.7%, 87.5%, 85.7% and 86.7% respectively in diagnosing CSOM with cholesteatoma. HRCT presented sensitivity and specificity of 85.7% and 87.5% in identification of malleus erosion, sensitivity and specificity of 86.7% and 80%, in the identification of incus erosion. HRCT showed the specificity of 85% with relatively low sensitivity of 70% in identification of erosion of stapes. HRCT showed a sensitivity of 100% and specificity of 85.7%. HRCT presented sensitivity and specificity of 83.3% and 95.8% in diagnosing tegmen tympanum erosion. HRCT showed the highest sensitivity (100%) and specificity (100%) in diagnosing erosion of sigmoid sinus plate and mastoid cortex. HRCT showed relatively low sensitivity of 66.7% and 75% in diagnosing erosion of LSCC and facial canal respectively. HRCT detected soft tissue mass in the middle ear/mastoid in all 30 patients of CSOM. Hence, the sensitivity, specificity, positive predictive value and negative predictive value of HRCT for soft tissue mass in the middle ear and mastoid, all were 100%.Conclusion: The HRCT has a valuable role in preoperative evaluation of a case of CSOM. It has high sensitivity in diagnosing CSOM with cholesteatoma. However, HRCT has relatively low sensitivity for LSCC and facial nerve canal erosion.